1989
DOI: 10.1111/j.1476-5381.1989.tb12656.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of tetrahydroaminoacridine‐evoked release of endogenous 5‐hydroxytryptamine and dopamine from rat brain tissue prisms

Abstract: 1 Tetrahydroaminoacridine (THA) is an acetylcholinesterase (AChE) inhibitor which may have a greater therapeutic effect in Alzheimer-type dementia (ATD) than other cholinergic agents. This suggests possible non-cholinergic properties. We have therefore studied the effects of THA on the release of endogenous 5-hydroxytryptamine (5-HT) from rat cortical prisms and dopamine from striatal prisms. 2 In the presence of K+ (1 mM), THA stimulated release of both 5-HT and dopamine. THA (100pM)-evoked monoamine release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
6
19
0
Order By: Relevance
“…The doses of THA used in this experiment are sufficient to produce a cognitive-enhancing effect in an animal model (Hagan et al 1989). The increase in brain NA, DA and 5-HT turnover produced by THA in the present study is consistent with previous studies that demonstrated a THA-induced increase in the release of endogenous DA and 5-HT from rat brain tissue prisms (Robinson et al 1989) and [3H]NA from rat cortex slices (Drukarch et al 1988). Furthermore, pretreatment with MEC (2.0mg/kg) completely blocked the THA-induced increase in NA and 5-HT turnover, but only partially blocked DA turnover.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The doses of THA used in this experiment are sufficient to produce a cognitive-enhancing effect in an animal model (Hagan et al 1989). The increase in brain NA, DA and 5-HT turnover produced by THA in the present study is consistent with previous studies that demonstrated a THA-induced increase in the release of endogenous DA and 5-HT from rat brain tissue prisms (Robinson et al 1989) and [3H]NA from rat cortex slices (Drukarch et al 1988). Furthermore, pretreatment with MEC (2.0mg/kg) completely blocked the THA-induced increase in NA and 5-HT turnover, but only partially blocked DA turnover.…”
Section: Discussionsupporting
confidence: 91%
“…However, whether this compound is effective in stimulating brain NA and/or 5-HT function has not been clarified. On the other hand, 9-amino-1,2,3,4-tetrahydroacridine (THA), an acetylcholine esterase (ACHE) inhibitor, which is used for the treatment of cognitive impairment in Alzheimer's disease, affects monoaminergic function (Adem et al 1989;Robinson et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, also the possibility that mechanism(s) other than AChE protection may be involved in THA antidotal action, deserves attention. It is well known that THA has a complicated pharmacology and exerts several actions besides interacting with cholinesterases (Rogawski 1987;Albin et al 1988;Davenport et al 1988;Hunter et al 1989;Robinson et al 1989;Peterson 1990;Thesleff et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Interest in this drug arises mainly from reports indicating that is effective in improving the clinical condition of certain patients with Alzheimer's disease (Summers et al 1989). Although there is growing evidence for other than AChE inhibitory actions (Albin et al 1988;Hunter et al 1989;Robinson et al 1989;Peterson 1990;Thesleff et al 1990), the opinion that THA exerts its beneficial effects primarily by temporarily inhibiting central AChE still seems to prevail over other hypotheses at the moment (Nielsen et al 1989). Previous studies have shown that THA and THA derivatives may exert direct protective action on AChE from various sources against inhibition by organophosphorus compounds (Patocka et al 1976;Bajgar et al 1983;Wu and Yang 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The observed changes in binding might probably be due to a direct milameline action on muscarinic autoreceptors which generates an altered concentration of acetylcholine and dopamine in the synaptic cleft. Increased dopamine levels have earlier been measured following the reversible choline esterase inhibitor tacrine in vitro [29, 30]and when perfused into striatal tissue of freely moving rats using microdialysis [31]. The increased synaptic concentrations of dopamine found in those studies correlated with the enhanced acetylcholine concentrations as well as to a direct action of tacrine on muscarinic and nicotinic heteroreceptors.…”
Section: Discussionmentioning
confidence: 96%